Perancangan Sistem Informasi Inventaris pada PT. Rejoso Manis Indo Menggunakan Metode Rapid Application Development - Panky Yoga Pratama; Abd. Charis Fauzan; Tito Prabowo (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
Technology that cannot be stopped and is increasingly developing requires companies like PT. Rejoso Manis Indo to adopt a more sophisticated and efficient system. This company's still manual inventory management process faces various problems, such as recording errors, lost or damaged data, and low efficiency. Difficulty tracking the status of goods also results in inaccurate data. This research aims to design an inventory information system using the Rapid Application Development (RAD) method which involves users at every stage of development. Data was collected through Likert scale questionnaires, interviews, and literature studies. This system was implemented using PHP CodeIgniter, and MySQL, and checked using the System Usability Scale (SUS) and black box testing. The research results show that the developed inventory information system increases effectiveness and efficiency, with a user satisfaction level of 77 with a value of B (Good). In conclusion, this system is effective in overcoming inventory problems at PT. Rejoso Manis Indo, although further research is needed to involve more users from various departments and examine the security and scalability aspects of the system.